Regulatory T cell inhibition by dasatinib is associated with natural killer cell differentiation and a favorable molecular response—The final results of the D-first study. (March 2018) - Najima, Yuho; Yoshida, Chikashi; Iriyama, Noriyoshi; Fujisawa, Shin; Wakita, Hisashi; Chiba, Shigeru; Okamoto, Shinichiro; Kawakami, Kimihiro; Takezako, Naoki; Kumagai, Takashi; Ohyashiki, Kazuma; Taguchi, Jun; et al.
Highlights: The first-line use of dasatinib for Japanese CML-CP patients was validated. The inhibition of Treg by dasatinib was associated with the achievement of DMR. The Treg inhibition was closely correlated with NK cell differentiation degree. Abstract: We evaluated the effects of regulatory T cell (Treg) inhibition during dasatinib treatment on the anticancer immune response, particularly on natural killer (NK) cells and cytotoxic T lymphocytes (CTLs). Fifty-two newly diagnosed Japanese patients with chronic myeloid leukemia (CML) in the chronic phase were enrolled in the D-first study; all received 100 mg of dasatinib once daily and were followed for at least 36 months. The cumulative deep molecular response (DMR, MR4) rate was 65% by 36 months; the 3-year overall survival was 96%. CD4 + T cell counts were stable, whereas the proportion of CD4 + CD25 + CD127 low (Treg) cells decreased in a time-dependent manner. The DMR rate by18 months was significantly better in low Treg patients (<5.7% at 12 months) compared to the remaining patients (odds ratio 4.07). NK cell and CTL counts at several time points were inversely correlated with Treg counts. Furthermore, the degree of NK cell differentiation (CD3 − CD57 + /CD3 − CD56 + ) was closely and inversely correlated with the proportion of Treg cells throughout the observation period, and showed a gradually increasing trend. In conclusion, our results demonstrate that Treg inhibition by dasatinib contributes to better treatment response through enhancement of the immune system, particularly via NK cell differentiation.